(untitled) (Research, Society and Development, 2022)
Introduction: Parents are the greatest source of influence on their children between the ages of 0 and 12, and it is up to them to provide adequate education in order to generate a better quality of life. It is with them that children start their oral health care, depending on the knowledge of ideal oral hygiene, avoiding diseases that affect quality of life. Objective: Evaluate the care and behavior of parents or guardians that influence the quality of oral health of their children. Materials and Methods: Exploratory research was adopted, based on national and international journals and recommendations from government institutions. The following selection criteria were used: references that addressed the issue of parental influence on children’s oral health and the consequences of inadequate oral hygiene. Results and discussions: Note that in addition to the relationship of influence of parents and guardians, there are other factors that generated the quality of oral health in the family environment. Conclusion: It is necessary to promote strategies to promote children’s oral health, including preventive measures of parental supervision, education present in academic training, motivation of professionals and performance of dental prenatal care.